2007
DOI: 10.1111/j.1471-4159.2007.04937.x
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical recruitment by AMPA but not staurosporine of pro‐apoptotic mitochondrial signaling in cultured cortical neurons: evidence for caspase‐dependent/independent cross‐talk

Abstract: Excitotoxicity mediated via the (S)-a-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) subtype of receptor for L-glutamate contributes to various neuropathologies involving acute brain injury and chronic degenerative disorders. In this study, AMPA-induced neuronal injury and staurosporine (STS)-mediated apoptosis were compared in primary neuronal cultures of murine cerebral cortex by analyzing indices up-and downstream of mitochondrial activation. AMPAmediated apoptosis involved induction of Bax, loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(66 citation statements)
references
References 51 publications
(165 reference statements)
5
61
0
Order By: Relevance
“…Staurosporine (STS), a classical apoptotic stimulus that has been previously widely characterized to induce apoptosis in several different cell types including primary neuronal cultures, [25][26][27] was used to promote apoptosis in primary cultures of cortical neurons. In the present experiments, 1 μM STS induced neuronal death as demonstrated by a progressive increase in the number of pyknotic nuclei from 6 h of STS treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Staurosporine (STS), a classical apoptotic stimulus that has been previously widely characterized to induce apoptosis in several different cell types including primary neuronal cultures, [25][26][27] was used to promote apoptosis in primary cultures of cortical neurons. In the present experiments, 1 μM STS induced neuronal death as demonstrated by a progressive increase in the number of pyknotic nuclei from 6 h of STS treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our observations on caspase-3 and AIF release and protection by caspase-inhibition agree with previous studies on STS-treated on cortical neurons. 25,26 Only a few studies have reported STSinduced autophagy in unmodified cells 34,35 especially in cortical neurons, 36 but in specific conditions, such as in fibroblast mutants incompetent for apoptosis, STS has been reported to cause autophagic cell death that is blocked by 3-MA or by knockdown of Atg5 or Beclin 1.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, whereas staurosporine treatment elicited an apoptotic injury, 25 glutamate exposure triggered a nonapoptotic, presumably necrotic injury in neuronal culture. 26 Despite eliciting different types of injury, both staurosporine and glutamate treatment caused an immediate increase in tPA-binding, in line with our initial observation that tPA binds to nonviable neurons in culture ( Figure 1C,E).…”
Section: Tpa Binds To Injured Neurons In Vitromentioning
confidence: 92%
“…Knockdown of these proteins via short interfering RNA (siRNA) protects these cells from paraquat treatment. Translocation of Bax and Bak to the OMM initiates outer mitochondrial membrane permeabilization (OMMP), resulting in the redistribution of pro-apoptotic factors from the mitochondrial IMS, such as cyt c, Smac/DIABLO and HtrA2/Omi which are essential for the activation of downstream effector caspase-3 and caspase-7, ultimately leading to neuronal cell death [86][87][88].…”
Section: Chronic Oxidative Stress and Pcd: Apoptosis And Autophagymentioning
confidence: 99%